Kontribusi Tourist Experience Terhadap Revisit Intention Wisatawan di Kepulauan Seribu DKI Jakarta - Hery Soesanto; R. Kusherdyana; Syaeful Muslim; R. Soendjana A Suganda (Tourism Scientific Journal, 2020)
This study aims to reveal how much the contribution of tourist experience to revisit intention in Kepulauan Seribu Jakarta. The research method used is explanatory survey. The sample members were tourists who visited Kepulauan Seribu with a size of 169 people selected by incidental sampling technique. Result of research indicates there is contribution of tourist experience to revisit intention of tourist in Kepulauan Seribu. The contributing variables are hedonic and relational.